Stent migration after right ventricular outflow tract stenting in the severe cyanotic Tetralogy of Fallot case - Tamaki Hayashi; Saleem Akhtar; Mazeni Alwi (Wolters Kluwer Medknow Publications, 2017)
We report our experience with a stent migration after right ventricle outflow tract stenting and converted to patent ductus arteriosus stenting in Tetralogy of Fallot (TOF) with severe infundibular stenosis. Finally, the patient achieved to TOF repair, and the migrated stent was removed without any complication.